PTH-071 Prospective anti-tnf withdrawal in quiescent crohn's disease – 12 month clinical outcomes. (22nd June 2015) - Squires, S; Boal, A; Hamid, R; Heydtmann, M; Naismith, G
Abstract : Introduction: Anti Tumour Necrosis Factor (anti TNF) is an effective yet expensive intervention in Crohn's Disease. 1 The STORI trial outcomes suggest that withdrawal of Infliximab therapy may be safe. 2 Method: Between April and July 2013 all those attending Paisley RAH and the Vale of Leven Hospitals with Crohn's disease on anti TNF had their cases evaluated at 3 'virtual' clinics. Assessment tool criteria for quiescent disease (absence of symptoms, no recent escalation, established 2nd line therapy and absence of active inflammation on endoscopy or radiology) were used to identify those in clinical remission. 8 individuals were offered a withdrawal from anti TNF therapy with optimisation of 2nd line therapy as appropriate. 12 month clinical outcomes were prospectively recorded. Results: Of 36 individuals identified, 8 patients were deemed to be in remission at the time of reassessment and were therefore withdrawn. 6 of those patients maintained a remission for the following twelve months. 1 patient relapsed within 1 month of withdrawal and another relapsed 11 months after withdrawal. Both achieved clinical remission on prompt retreatment. The cost savings in this study for 1 year are £83756.18. Conclusion: Withdrawing anti TNF therapy, in the context of quiescent Crohn's Disease, appears to be safe and effective, providing there are mechanisms in place for prompt assessment and reintroduction of therapy. The cost savings by using this strategy can be substantial. Disclosure of interest: None Declared. References: NICE Guidelines – CE technology appraisals [TA187] Published date: May 2010 Infliximab (review) and Adalimumab for the treatment of Crohn's disease Louis E, Vernier-Massouille G, Grimaud J et al . Infliximab discontinuation in Crohn's disease patients in stable remission on combined therapy with immunosuppressors. Gut 2008;57 :A66